Economic and Environmental Drivers of Migration: Insights from Rural Cambodia - HQ, WorldFish (WorldFish, 2024)
This study builds on the context of Cambodia’s labor market dynamics, migration trends, and climate change impacts based on a 2023 survey of 518 households across five provinces. Most households have a higher proportion of income earners than dependents, but economically vulnerable groups, such as IDPoor and female-headed households, face significant challenges, including higher dependency ratios and lower incomes. Female-headed households rely heavily on women, who contribute more workdays but face economic and gender disparities. Climate shocks, such as droughts and floods, disrupt agriculture, exacerbate economic instability, and force migration as a survival strategy, especially among households with limited coping mechanisms. Migration provides essential remittances but highlights systemic vulnerabilities. To address these issues, the study recommends livelihood diversification, improved access to education and resources for women, and investments in climate-resilient infrastructure and disaster preparedness. These strategies aim to reduce migration reliance and promote sustainable rural development in Cambodia.